Sistem Informasi Pendaftaran di RSIA Prima Qonita Menggunakan Php Mysql Berbasis Web - Uci Juwita Agustiani; Hendrayudi; Rusidi (Universitas Mahakarya Asia, 2021)
Along with the development of the world of technology and information, the website is a medium of information and promotion that offers convenience in presenting information and registration of RSIA Prima Qonita who do not yet have a website facility to provide information to the wider community. This study aims to register RSIA Prima Qonita which can later be userful for all parties. The data collection method used for making this website uses the interview, reference,and observation methods.making this wbsite using visual studio and PHP Mysql as the database, the website that will later be designed consists of several pages including the home page, list, dashboard, rooms, services, logins, patients, drugs and payments. The results of this study are in the form of a registration information system for the Prima Qonita Mother and Child Hospital website and Mysql applications in order to facilitate information and ordering. Key : Information System, Website, Registration, Php Mysql and Database